2021
DOI: 10.3390/ijms22073438
|View full text |Cite
|
Sign up to set email alerts
|

A Degeneration Gradient of Poplar Trees Contributes to the Taxonomic, Functional, and Resistome Diversity of Bacterial Communities in Rhizosphere Soils

Abstract: Bacterial communities associated with roots influence the health and nutrition of the host plant. However, the microbiome discrepancy are not well understood under different healthy conditions. Here, we tested the hypothesis that rhizosphere soil microbial diversity and function varies along a degeneration gradient of poplar, with a focus on plant growth promoting bacteria (PGPB) and antibiotic resistance genes. Comprehensive metagenomic analysis including taxonomic investigation, functional detection, and ARG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 78 publications
0
6
1
Order By: Relevance
“…The top discriminative features are shown in Figure 5 . Of these, the classifiable genus-level features differentially more abundant in OL were: Acidibacter , highly tolerant to transition metals, as well as to arsenic [ 99 ]; Acidobacterium , related to organic matter transformation in forest soils [ 100 ], which is considered an indicator for soil fertility and plant health [ 101 ]; Desulfohalophilus , described as extreme halophilic sulfate- and arsenate-respiring bacteria [ 102 ]; Edaphobacter , whose presence has been reported in heavy metal contaminated soils [ 103 ] and more recently indicated as a potential source for bioelectricity production from sludge matrices [ 104 ]; and Paraburkholderia , identified as the main nitrogen-fixing microsymbionts of Mimosa tenuiflora from Caatinga (tropical dry forests) [ 105 ]. Actinokineospora was differentially more abundant in OH.…”
Section: Resultsmentioning
confidence: 99%
“…The top discriminative features are shown in Figure 5 . Of these, the classifiable genus-level features differentially more abundant in OL were: Acidibacter , highly tolerant to transition metals, as well as to arsenic [ 99 ]; Acidobacterium , related to organic matter transformation in forest soils [ 100 ], which is considered an indicator for soil fertility and plant health [ 101 ]; Desulfohalophilus , described as extreme halophilic sulfate- and arsenate-respiring bacteria [ 102 ]; Edaphobacter , whose presence has been reported in heavy metal contaminated soils [ 103 ] and more recently indicated as a potential source for bioelectricity production from sludge matrices [ 104 ]; and Paraburkholderia , identified as the main nitrogen-fixing microsymbionts of Mimosa tenuiflora from Caatinga (tropical dry forests) [ 105 ]. Actinokineospora was differentially more abundant in OH.…”
Section: Resultsmentioning
confidence: 99%
“…PGPB has shown that they can maintain genes for antibiotic and metal resistance [ 43 ]. In addition, some research has indicated that antibiotic resistance in plants can be a significant concern in the use of PGPB in agriculture [ 44 ].…”
Section: Plant Beneficial Microorganismsmentioning
confidence: 99%
“…Further, as the rhizosphere of the infected tree begins to degrade, these taxa may thrive because of their unique abilities to breakdown complex plant root materials. Several studies have observed changes in bacterial communities associated with declines in plant communities [122][123][124].…”
Section: Discussionmentioning
confidence: 99%